2018
DOI: 10.1007/s10616-017-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Friedelane, isolated from Pouzolzia indica Gaud. exhibits toxic effect against melanoma

Abstract: Melanoma is a predominant cause of skin cancer-related deaths. It was reported that, the methanolic extract of Pouzolzia Indica (P. indica) on chromatography gave five compounds (1-hentriacontanyl palmitate, myricyl alcohol, 6,7-dimethoxycoumarin, trichadonic acid and friedelane), which inhibited the acute promyelocytic leukemia cell lines, NB4, and HT93A. Friedelane was extracted as active compound from methanolic extract of P. indica. In this study, friedelane was tested on murine metastatic B16F10 and B16BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[3] Phytochemical studies on Pouzolzia genus revealed the presence of norlignans, prenylated isoflavones, triterpenes which have shown anti-inflammation and cytotoxic activities. [4,5] In our previous report, several norlignans were identified from aerial parts of P. sanguinea. Their chemical structures were remarkable not only by the loss of one carbon in lignan skeleton but also the presence of an additional benzene ring.…”
Section: Introductionmentioning
confidence: 93%
“…[3] Phytochemical studies on Pouzolzia genus revealed the presence of norlignans, prenylated isoflavones, triterpenes which have shown anti-inflammation and cytotoxic activities. [4,5] In our previous report, several norlignans were identified from aerial parts of P. sanguinea. Their chemical structures were remarkable not only by the loss of one carbon in lignan skeleton but also the presence of an additional benzene ring.…”
Section: Introductionmentioning
confidence: 93%
“…Pauzolzia indica Gaud (Urticaceae) is prevalent in tropical regions of the globe. Some communities in southern India utilize it in traditional medicine for female infertility, cancer, inflammation, emmenagogue, pesticide, and antisnake venom [106] …”
Section: Main Types Of Triterpenoidsmentioning
confidence: 99%
“…Friedelane was produced from a methanol extract of aerial portions of P. indica , which had a significant cytotoxic impact against metastatic B16F10 and B16BL6 melanoma mice cell lines at a dose of 10 μM. Friedelane also inhibits proliferation and promotes apoptosis via the mitochondrial pathway, as an increase in the expression of the Bax, cytochrome C, and BAD proteins, as well as the caspase three proteins [106] . Endodesmia calophylloides Benth., the single tree species of the genus Endodesmia, family Guttiferae, an African monotypic genus found in Angola, Gabon, Cameroon, and Nigeria, is not employed in any traditional medical system.…”
Section: Main Types Of Triterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In addition, those compounds exhibited the anti-bacterial, antioxidant, and anti-inflammatory activities. [5,6] However, phytochemical and biological studies of P. sanguinea have not been reported yet. This paper reported the isolation and structural elucidation of five norlignans from P. sanguinea.…”
Section: Introductionmentioning
confidence: 99%